ZANU’s External Networks 1963–1979: An Appraisal - Mazarire, Gerald Chikozho (Routledge, 2021)
The Zimbabwe African National Union (ZANU) emerged from the smouldering ashes of the intra-party violence that followed its break away from the Zimbabwe African People’s Union (ZAPU) in 1963 and the clampdown by Rhodesian authorities. Its structures were barely consolidated when it was banned in 1964, and its efforts in exile suffered a crisis of recognition, as the key sponsors of African liberation movements continued to view it as an ‘inauthentic’ and ‘separatist’ movement. This article traces the structures and strategies that ZANU used to manoeuvre through these obstacles to become a fully-fledged liberation movement by the mid 1970s. It pays particular attention to the work of individuals and organisations that facilitated this transformation by tracing a wide range of regional and international networks, including military, financial, humanitarian and diplomatic roles. The main sources are the growing corpus of oral reminiscences and published memoirs of the main players. It argues that ZANU was a beneficiary of the contradictions in the international solidarity movement. As it grew in stature, however, its own internal contradictions as a movement threatened to consume it and render the efforts and sacrifices of its exiles worthless. Yet, as the war escalated, these exile networks were the very basis on which an effective diplomatic offensive was launched, which complemented the successes that ZANU had in the battlefield. This aspect of the ZANU war effort is often conveniently omitted by ZANU itself.